2000
DOI: 10.3758/bf03212070
|View full text |Cite
|
Sign up to set email alerts
|

Attention and spatial selection: Electrophysiological evidence for modulation by perceptual load

Abstract: Behavioral data have suggested that perceptual load can modulate spatial selection by influencing the allocation of attentional resources at perceptual-level processing stages (Lavie& Tsal, 1994). To directly test this hypothesis, event-related potentials (ERPs) were recorded for both low-and highperceptual-load targets in a probabilistic spatial cuing paradigm. The results from three experiments showed that, as measured by the lateral occipital PI and Nl ERP components, the magnitude of spatially selective pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
132
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 51 publications
24
132
1
Order By: Relevance
“…Together, these findings support the notion that early processes are primarily engaged when perceptual load and task requirements are high (Handy & Mangun, 2000;Lavie, 1995Lavie, , 2005Lavie & Tsal, 1994;Luck, Woodman, & Vogel, 2000).…”
Section: Discussionsupporting
confidence: 72%
“…Together, these findings support the notion that early processes are primarily engaged when perceptual load and task requirements are high (Handy & Mangun, 2000;Lavie, 1995Lavie, , 2005Lavie & Tsal, 1994;Luck, Woodman, & Vogel, 2000).…”
Section: Discussionsupporting
confidence: 72%
“…Given that many previous studies have shown effects of voluntary attention at early stages of processing (e.g., Eimer, 1994b;Mangun & Hillyard, 1991), we do not suggest that the present results should be interpreted as evidence that voluntary and social orienting cannot affect these levels of processing. Rather, the present results lend further support to the argument that the effects of voluntary attention on early visual processing are sensitive to task demands and perceptual load (Handy & Mangun, 2000). Indeed, small and/or nonexistent effects of voluntary orienting on early sensory processing are not an uncommon finding when using a localization task (Eimer, 1994a;Prime & Ward, 2006), such as the one used in this study.…”
Section: Discussionsupporting
confidence: 59%
“…For example, some studies have found that gaze cuing enhances the amplitude of the target-evoked P1 component (e.g., Schuller & Rossion, 2001, while others have shown no evidence of amplitude modulation of early visual processing by social gaze cuing (Fichtenholtz, Hopfinger, Graham, Detwiler, & LaBar, 2007Magnée, Kahn, Cahn, & Kemner, 2011). Thus, it may be the case that the ERP effects of social gaze orienting may be sensitive to the perceptual and cognitive loads induced by the task and stimuli, as has been shown for voluntary attention (e.g., Eimer, 1994a;Handy & Mangun, 2000;Prime & Ward, 2006;Vogel & Luck, 2000). In addition, theories of attention based on overt behavior have often assumed multiple types of attention processes, and that some mechanisms may be differentially involved, depending on the task and stimulus parameters (see, e.g., Dosher, 1998, andPrinzmetal et al 2005).…”
mentioning
confidence: 94%
“…An enhancement of the P1 component occurs for all stimuli at a voluntarily attended location, arguing that it indexes focal spatial attention (e.g., Heinze, Luck, Mangun, & Hillyard, 1990;Luck, Fan, & Hillyard, 1993;Mangun & Hillyard, 1991). However, recent studies have shown that task demands can play a role in voluntary P1 attention effects (e.g., Eimer, 1994;Handy & Mangun, 2000). Handy & Mangun showed that the P1 attention effect was observed only when attention was induced to be strongly focused on the attended location (under conditions of high perceptual load).…”
mentioning
confidence: 99%